2019
DOI: 10.1051/fopen/2019010
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB signaling and crosstalk during carcinogenesis

Abstract: Transcription factors (TFs) are proteins that control the transcription of genetic information from DNA to mRNA by binding to specific DNA sequences either on their own or with other proteins as a complex. TFs thus support or suppress the recruitment of the corresponding RNA polymerase. In general, TFs are classified by structure or function. The TF, Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), is expressed in all cell types and tissues. NF-κB signaling and crosstalk are involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 400 publications
0
32
0
Order By: Relevance
“…NF-κB facilitates cancer progression by promoting cell cycle advances through the expression of the cyclin genes (D1, D2, D3, and DE) and c-myc [ 141 , 142 , 143 , 144 , 145 ], which play active roles in cell cycle progression. Additionally, NF-κB promotes the expression of cell adhesion proteins, like CD54, metalloproteinases involved in tumor invasion, and angiogenic factors such as the vascular endothelial growth factor [ 146 ]. By its part, STAT3 is a transcription factor involved in the Janus kinase/signal transducer and activator of transcription (JAK–STAT) signaling pathway whose hyperactivation also leads to tumor progression.…”
Section: Age-associated Diseases: Implication Of the Nlrp3 Inflammmentioning
confidence: 99%
“…NF-κB facilitates cancer progression by promoting cell cycle advances through the expression of the cyclin genes (D1, D2, D3, and DE) and c-myc [ 141 , 142 , 143 , 144 , 145 ], which play active roles in cell cycle progression. Additionally, NF-κB promotes the expression of cell adhesion proteins, like CD54, metalloproteinases involved in tumor invasion, and angiogenic factors such as the vascular endothelial growth factor [ 146 ]. By its part, STAT3 is a transcription factor involved in the Janus kinase/signal transducer and activator of transcription (JAK–STAT) signaling pathway whose hyperactivation also leads to tumor progression.…”
Section: Age-associated Diseases: Implication Of the Nlrp3 Inflammmentioning
confidence: 99%
“…In cervical cancer, HPV DNA integration in the host genome, genomic rearrangement, involving structural changes at the HPV DNA integration site, and the activation of replication at viral integrated sequences contribute to oncogenesis [121][122][123]. Genetic alterations which foster carcinogenesis involve DNA methylation and nucleotide polymorphisms.…”
Section: The Role Of Human Papillomavirus In Oncogenesismentioning
confidence: 99%
“…HPV infection also triggers inflammatory pathways, primarily targeting the central regulators of inflammation, the NF-κB, STAT3, and cyclooxygenase-prostaglandin (COX-PG) pathways. In oral cancer, HPV E6 activates the NF-κB pathway by interaction with p50, NF-kappa-B-inducing kinase (NIK), and TRAF-interacting protein; in parallel, E7 inhibits apoptosis by targeting TNF-α [123]. In cervical cancer, the HPV E6-mediated elevated activity of IL-17 and increased expression of IL-1β by HPV E7 activate NF-κB [124].…”
Section: The Role Of Human Papillomavirus In Oncogenesismentioning
confidence: 99%
“…Recent studies have also shown indirect evidence that NF-κB regulates the differentiation and function of osteoclasts through activation of the B-cell receptor to promote Bruton's tyrosine kinase and the inhibitor of nuclear factor-κB kinase expression in lymphocytes. While the latter induced Toll-like receptor 7 and 8 (TLR7/8) following stimulation of TNF transcription, KS99, a small molecule inhibitor of tubulin polymerisation, was found to block osteoclast differentiation and function (Brücher et al, 2019). Thus, the immune effects of NF-κB signalling associated with the regulation of AMPK requires further investigation.…”
Section: The Use Of Agents and Clinical Drugs To Regulate Ampk-mediatmentioning
confidence: 99%